Synvo Headphone - Nik Min, Nik Mohd Faris; Md Nasir, Siti Zulaikha; Ahmad Ridduan, Umi Nazirah; Ku Mohd Nazri, Ku Nuranis Nabilah; Azmi, Aefa Azwa (Academica Press Solutions, 2025)
The explosive growth of the internet gaming community around the world has converged players from various linguistic communities in the same space, whereas communication between them is hindered, which consequently has an impact on team coordination and also the gaming experience itself. This paper describes Synvo Headphones, a new technology incorporating real-time language translation to enable multiplayer game playing interaction. Using speech-to-text, natural language processing (NLP) and adaptive (noisy) reduction, these headphones offer an all-in-one cross-language communication solution for immersive, collaborative, global-driven gameplay among globally diverse gamers. Through a wide study, based on interviews with game play and industry view, the study discovers a number of critical pain points such as incompletion, discomfort and requester of controllability properties. The proposed solution emphasizes effective in-game communication, ergonomic usability to facilitate long-term use, and modular design for usability. This study advances the state-of-the-art in gaming peripherals by overcoming multilingual collaboration problems, towards the future of AI-powered interactive systems in the game industry and elsewhere.